Light Extraction: Efficiently Releasing the Trapped Energy Flow in White Organic Light‐Emitting Diodes with Multifunctional Nanofunnel Arrays (Adv. Funct. Mater. 18/2015). (May 2015) - Zhou, Lei; Ou, Qing‐Dong; Li, Yan‐Qing; Xiang, Heng‐Yang; Xu, Lu‐Hai; Chen, Jing‐De; Li, Chi; Shen, Su; Lee, Shuit‐Tong; Tang, Jian‐Xin
<x xml:space="preserve">Abstract</x> On page 2660, J. X. Tang and co‐workers demonstrate a powerful method for drastically releasing the trapped energy flow in conventional white organic light‐emitting diodes by implementing a unique quasi‐periodic subwavelength nanofunnel array via soft nanoimprinting litho‐graphy. Besides the substantial increase in efficiency over a broad bandwidth without any spectral distortion or angular dependence, this array affords an enticing capacity against scrubbing and the self‐cleaning feature, which are critical to the commercial viability in practical applications.